Elevation of Circulating miR-210 Participates in the Occurrence and Development of Type 2 Diabetes Mellitus and Its Complications - Xi Chen; Feng Tian; Zhilian Sun; Guoqing Zeng; Ping Tang (Journal of Diabetes Research)
Objective. Circulating miRNAs are acclaimed biomarkers to predict the occurrence and progression of type 2 diabetes mellitus (T2DM). This study is aimed at analyzing the correlation of circulating miR-210 level and obesity-associated T2DM and then investigating the underlying mechanism of circulating miR-210 in T2DM. Methods. Totally, 137 serum samples from patients with T2DM were collected; meanwhile, the demographic, general, and clinical hematological characteristics, disease history, and dietary patterns were recorded. The miR-210 level in exosomes from serum was detected by qRT-PCR. Then, the correlations of BMI or miR-210 level with patients’ clinical characteristics were analyzed. Furthermore, the miR-210 level was detected in T2DM related various cells under high glucose condition. Meanwhile, the expression of carbohydrate responsive element binding protein (ChREBP) and hypoxia-inducible factor 1α (HIF-1α) was measured by western blotting. Results. The miR-210 level in exosomes from serum was obviously elevated in the BMI>24 group compared with the BMI≤24 group. Higher BMI was correlated with abnormal lipid metabolism and impaired liver function as well as higher miR-210 level. Notably, higher miR-210 level was also correlated with abnormal lipid metabolism, disease history, and dietary patterns. In addition, compared with normal cells, high glucose increased the miR-210 level in exosomes from cell culture supernatants as well as cells in HUVEC, VSMC, RAW 264.7, 3 T3-L1, SMC, and Beta-TC-6 cells, while it reduced the expression of ChREBP and HIF-1α. Conclusions. Circulating miR-210 level was closely correlated with obesity-associated T2DM. Furthermore, higher miR-210 level might be implicated in the occurrence and development of T2DM and its complications.